Stimulus specificity of prostaglandin inhibition of rabbit polymorphonuclear leukocyte lysosomal enzyme release and superoxide anion production. - Fantone, J. C. (1984)
Prostaglandins (PGs) of the E series and PGI2 have been shown to inhibit acute inflammatory reactions in vivo and polymorphonuclear leukocyte (PMN), chemotaxis, lysosomal enzyme release, and superoxide anion (O-2) production in vitro. This inhibition of neutrophil stimulation by PGEs and PGI2 has been correlated with their ability to increase intracellular cyclic adenosine monophosphate (cAMP) levels. However, the mechanism(s) by which PGEs and PGI2 alter the complex biochemical and biophysical events associated with stimulus-response coupling in the neutrophil are not clear. It is reported here that both PGEs and PGI2 in micromolar concentrations inhibit formyl-methionyl-leucyl-phenylalanine (FMLP)- and zymosan-induced lysosomal enzyme secretion and superoxide anion production in a dose-dependent manner. No preincubation time of PMNs with the prostaglandins is required for inhibition. Addition of PGEs 10 seconds or later after FMLP stimulation does not alter the biologic response of the neutrophils to the stimulus, suggesting that the prostaglandin inhibition effects early events associated with stimulus-response coupling in the neutrophil. Prostaglandin inhibition of lysosomal enzyme release by the calcium ionophore A23187 was overcome by increasing the extracellular ionophore and/or calcium concentration, suggesting that PGs may modulate intracellular free calcium levels in a manner similar to that observed with platelets. Inhibition of phorbol myristate acetate (PMA)-induced neutrophil lysosomal enzyme secretion by PGEs and PGI2 was overcome by increasing concentrations of PMA. However, neither PGEs nor PGI2 altered O-2 production by PMA-treated neutrophils. These data indicate a dissociation between PMA-stimulated O-2 production and lysosomal enzyme release. These findings are consistent with the hypothesis that inhibition of neutrophil stimulation by PGEs and PGI2 is a result of increased intracellular cyclic AMP levels and modulation of calcium-dependent events. In addition, the data indicate that there are at least two mechanisms by which PMNs can be stimulated to produce O-2, one inhibited by PGEs and PGI2 and a second independent of prostaglandin modulation.